The analysis of semiconducting charateristic of rice husk-based carbon nanomaterial bio-activated by pineapple peel juice - Ni Made Dwidiani; Ngakan Putu Gede Suardana; I Nyoman Gede Wardana; Willy Satrio Nugroho; I Gusti Ketut Puja; Wayan Nata Septiadi; I Gusti Ngurah Nitya Santhiarsa; Si Putu Gede Gunawan Tista (Mechanical Engineering for Society and Industry, 2025)
This study investigates the synthesis and characterization of semiconducting materials derived from rice husk bio-activated by pineapple peel juice, presenting an eco-friendly and sustainable approach. The organic photo-active semiconducting material from rice husk ash (RHA) is synthesized. RHA was activated by immersion in the pineapple juice solution. Distinct structural disparities among RHA, Sunken Carbon nanomaterial (SCNM), and Floating Carbon Nanomaterial (FCNM) materials are revealed through SEM imaging, showcasing the tailored nature of each material. The SEM images also indicate the role of bromelain from the pineapple juice to provide defects on the RHA carbon surface. The crack on the nano particles on the surface of SCNM and FCNM were formed due to the bromelain electrostatic interaction with the surface. Elemental analysis indicates a higher probability of CuO and Si presence in SCNM, suggesting its potential for semiconductor extraction. The Cu to Si ratio implies photoactivity, confirmed by UV-Vis characterization showing absorption peaks in the UV region. FTIR analysis highlights enhanced polar interactions in SCNM and FCNM, attributed to the activation process involving bromelain in pineapple juice. The photoelectric effect testing shows FCNM and SCNM generates more electrical current as exposed to light which. The current was generated due to the electron transport phenomenon of CuO and Si content triggered by photons. The study provides insights into the materials' molecular structures and potential applications in sensors, energy devices, and semiconductor-related technologies, leveraging the unique properties of bio-derived nanomaterials for practical implementation.